Cottonoid Sliders: A Simple and Cost-Effective Tool for Retractorless Intracranial Surgery. Issue 4 (1st May 2020) - Shao, Jianning; Borghei-Razavi, Hamid; Kshettry, Varun R; Lim, Michael; Recinos, Pablo F
Abstract: BACKGROUND AND IMPORTANCE: Retraction injury can result in significant complications during intracranial operations. Alternative surgical techniques to minimize retraction pressure and duration of retraction can minimize the risk of retraction injury. We describe the use of a cottonoid "slider, " which is a simple, cost-effective modification of a commonly used cottonoid, in multiple applications. CLINICAL PRESENTATION: The cottonoid sliders are constructed preoperatively by overlaying an adhesive plastic incision drape on one side of a dry cottonoid patty and trimming the edges to fit the form of the cottonoid. Intraoperatively, the sliders can slide across the parenchymal surface atraumatically and are used for gentle retraction to expose desired areas. In addition, suction may be placed on the slider to clear fluid from the operative view. The plastic side of the slider prevents adherence to the parenchymal surface. Retractorless surgical techniques have been developed to minimize risk of retractor associated injury in intracranial surgery by reducing retraction pressure and duration. Given that the cottonoid sliders glide along the parenchyma, do not stick, and are used for dynamic retraction, the main objectives to minimize retraction injury can be met while not compromising operative efficiency. CONCLUSION: Cottonoid sliders are a simple and cost-effective method of providing gentle exposure during intracranial surgery. This technique represents a valuable and cost-effective addition to the neurosurgical armamentarium.